2023
DOI: 10.3390/su15075708
|View full text |Cite
|
Sign up to set email alerts
|

Research on Time to Market and Pricing of Platform Products in a Competitive Environment

Abstract: Platforms are gradually becoming important business organization models, and platforms with bilateral market characteristics such as payment platforms and online shopping platforms are gradually penetrating people’s lives. Freemium content mostly exists in particular platforms such as online video platforms, etc. Platforms need to balance upstream and downstream markets when formulating strategies. This paper is the first to explore the time-to-market and pricing strategies of products in bilateral markets. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Numerous recovery strategies have been proposed in the wake of the crisis. Authors [41] suggested strategies for acquiring competitive advantages, such as adopting new pricing models, collaborating with competitors, and adjusting customer offerings. Ratten [42] advocated for innovative and forward-thinking measures to tackle the COVID-19 pandemic.…”
Section: Crisis Recovery Strategies and Market Opennessmentioning
confidence: 99%
“…Numerous recovery strategies have been proposed in the wake of the crisis. Authors [41] suggested strategies for acquiring competitive advantages, such as adopting new pricing models, collaborating with competitors, and adjusting customer offerings. Ratten [42] advocated for innovative and forward-thinking measures to tackle the COVID-19 pandemic.…”
Section: Crisis Recovery Strategies and Market Opennessmentioning
confidence: 99%